The Influence of Differentiated Learning and Models Problem Based Learning on Mathematical Problem-Solving Ability at SDN 5 Gondang - Upik Ramadani; Raden Sumiadi; Ardi Dwi Susandi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This research is inspired by the importance of mathematical problem-solving skills for elementary school students and the need for innovation in learning approaches that can accommodate the diversity of students' learning needs. This study aims to determine the effect of implementing differentiated instruction and the Problem Based Learning (PBL) model on the mathematical problem-solving abilities of fifth-grade students at SDN 5 Gondang. The research method used is quantitative with a quasi-experimental design. The population of this study consisted of all fifth-grade students at SDN 5 Gondang. The data collection instruments included a test instrument to measure mathematical problem-solving abilities and non-test instruments in the form of observation sheets and analysis of student worksheets based on differentiated instruction and the PBL model. Data analysis was conducted using SPSS version 31 software through simple linear regression tests. The results showed that: 1) There is a significant difference in problem-solving abilities between students in experimental class 1 (differentiated instruction) and experimental class 2 (PBL model). The significance value obtained through a two-sided test was 0.024 < 0.05, thus it can be stated that there is a statistically significant difference between the problem-solving abilities of students taught using differentiated instruction and those taught using the PBL model. 2) The use of differentiated instruction in experimental class 1 proved to have an effect on students' problem-solving abilities, as indicated by an F-value of 9.480 with a significance level of 0.006 (<0.05). This confirms that there is an effect of the differentiated instruction variable (X) on the problem-solving ability variable (Y). 3) The application of the PBL model in experimental class 2 significantly influenced students' critical thinking skills. An F-value of 11.918 was obtained with a significance value (Sig.) of 0.003. Since the significance value is less than 0.05.